Z-Scheme Photocatalyst Constructed by Natural Attapulgite and Upconversion Rare Earth Materials for Desulfurization - Wu, Fengqin; Li, Xiazhang; Zhang, Haiguang; Zuo, Shixiang; Yao, Chao (Frontiers in Chemistry, 2018)
The Er3+:CeO2/ATP (attapulgite) nanocomposites were prepared by a facile precipitation method. The samples were characterized by various measurements. XRD and TEM showed that Er3+:CeO2 nanoparticles were well-crystallized and loaded on the surface of ATP. The visible light was converted into ultraviolet light by Er3+:CeO2 as evidenced by upconversion photoluminance (PL) analysis. The mass ratio of Er3+:CeO2 to ATP on the desulfurization efficiency was investigated. Results showed that the desulfurization rate reached 87% under 4 h visible light irradiation when the mass ratio was 4:10. The mechanism was put forward as follows. Er3+:CeO2 and ATP formed Z-scheme heterostructure intermediated by oxygen vacancy, leading to the enhanced separation of photogenerated charges and preservation of high oxidation-reduction potential, both of which favored for the generation of radicals to oxidize sulfur species.